Probing the compartmentalization of HIV-1 in the central nervous system through its neutralization properties. - Karl Stefic; Antoine Chaillon; Mélanie Bouvin-Pley; Alain Moreau; Martine Braibant; Frédéric Bastides; Guillaume Gras; Louis Bernard; Francis Barin (PLoS ONE, 2017)
Compartmentalization of HIV-1 has been observed in the cerebrospinal fluid (CSF) of patients at different clinical stages. Considering the low permeability of the blood-brain barrier, we wondered if a reduced selective pressure by neutralizing antibodies (NAb) in the central nervous system (CNS) could favor the evolution of NAb-sensitive viruses in this compartment. Single genome amplification (SGA) was used to sequence full-length HIV-1 envelope variants (453 sequences) from paired CSF and blood plasma samples in 9 subjects infected by HIV variants of various clades and suffering from diverse neurologic disorders. Dynamics of viral evolution were evaluated with a bayesian coalescent approach for individuals with longitudinal samples. Pseudotyped viruses expressing envelope glycoproteins variants representative of the quasi-species present in each compartment were generated, and their sensitivity to autologous neutralization, broadly neutralizing antibodies (bNAbs) and entry inhibitors was assessed. Significant compartmentalization of HIV populations between blood and CSF were detected in 5 out of 9 subjects. Some of the previously described genetic determinants for compartmentalization in the CNS were observed regardless of the HIV-1 clade. There was no difference of sensitivity to autologous neutralization between blood- and CSF-variants, even for subjects with compartmentalization, suggesting that selective pressure by autologous NAb is not the main driver of HIV evolution in the CNS. However, we observed major differences of sensitivity to sCD4 or to at least one bNAb targeting either the N160-V1V2 site, the N332-V3 site or the CD4bs, between blood- and CSF-variants in all cases. In particular, HIV-1 variants present in the CSF were more resistant to bNAbs than their blood counterpart in some cases. Considering the possible migration from CSF to blood, the CNS could be a reservoir of bNAb resistant viruses, an observation that should be considered for immunotherapeutic approaches.